Rectoral Leadership and Lecturer Performance in Higher Education Institutions - Ganjar Winata; Irawan Suprapto (BRIDGE : The Multidisciplinary Research Portal, 2025)
Effective leadership at the rectoral level plays a strategic role in shaping lecturer performance and institutional effectiveness in higher education. This study explores how rectoral leadership practices influence lecturer performance within a university context, drawing on perspectives of transformational, bureaucratic, and value-based leadership. Employing a qualitative case study design within an interpretivist paradigm, data were collected through in-depth interviews, participant observation, and document analysis involving university leaders, academic staff, and institutional records. Thematic analysis was applied to identify patterns of leadership practices related to motivation, performance management, and institutional support. The findings indicate that rectoral leadership contributes to lecturer performance primarily through structured coordination mechanisms, value-driven motivational communication, and the delegation of performance-related programs across institutional units. Leadership practices emphasize alignment with core academic responsibilities, including teaching, research, community service, and the integration of institutional values. Although leadership implementation is largely hierarchical, it is perceived positively due to its clarity of vision, moral legitimacy, and consistency with organizational culture. The study contributes to higher education leadership literature by providing empirical insights into how rectoral leadership functions as a multidimensional process that combines strategic direction, bureaucratic coordination, and value-based engagement to support lecturer performance. However, the findings are limited by their single-case design and context specificity. Future research is recommended to adopt comparative or multi-site approaches and to incorporate mediating factors such as organizational culture, job satisfaction, and academic motivation to further explain leadership–performance dynamics in higher education.